EVALUASI QUANTITY TAKE OFF MENGGUNAKAN AUTODESK REVIT PADA PEKERJAAN STRUKTUR BAJA PROYEK PEMBANGUNAN GEDUNG KANTOR PT. TRI KANIGARA GROUP - Ari Wibowo; Michella Beatrix (LPPM Universitas Abdurrab, 2024)
With the development of technology, the use of BIM (Building Information Modeling) software such as Autodesk Revit is becoming increasingly common in the construction industry. Quantity Take Off (QTO) in Autodesk Revit is the process of calculating and identifying the amount of construction materials needed for a project based on a 3D model created using the Autodesk Revit software. This study aims to evaluate the use of steel structural materials and the estimated price generated through Autodesk Revit. In the QTO calculation using Autodesk Revit, the results are the volume of WF column work of 18,117.54 kg, the volume of WF beam work of 16,084.15 kg, and the volume of nut bolt work reaching 1,894 pieces. Furthermore, the estimated cost of work is also generated by Autodesk Revit, with the cost of WF column work of Rp. 389,527,110,-, the cost of WF beam work of Rp. 345,809,225,-, and the cost of nut bolt work of Rp. 52,085,000,-. This evaluation aims to identify the accuracy and efficiency of QTO calculations using Autodesk Revit.